Food safety, quality assurance, and global trade : concerns and strategies - Singh, S. P. (Professor of veterinary medicine); G.B. Pant University of Agriculture and Technology. Department of Veterinary Public Health; Michigan State University. College of Veterinary Medicine (Lucknow : International Book Distributing Co., 2009)
Contributed articles.
"In collaboration with Department of Veterinary Public Health, College of Veterinary & Animal Sciences, Pantnagar & College of Veterinary Medicine, Michigan State University, East Lansing, USA"--Cover.
Includes bibliographical references.
Keywords: Food -- Safety measures; Food -- Quality; Food industry and trade -- Management